1978
DOI: 10.1111/j.1399-3054.1978.tb02561.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic Uptake of Amino Acids by Barley Roots

Abstract: Concentration-dependence and other characteristics of uptake of •'H-labeled L-lysine, L-methionine and L-proline by excised roots of barley {Hordeum vulgare L.) were studied. Use of relatively short uptake and wash periods and low solute concentrations ensured good estimates of influx across the plasmalemma.Uptake in the range of 10"' M -6,3 x 10"^ M can be precisely represented by four or five phases of single, multiphasic mechanisms. The mechanisms appear to be relatively specific as judged from the competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 19 publications
(17 reference statements)
7
55
0
Order By: Relevance
“…Implicit in these studies is the assumption that plants can readily take up amino acids and peptides. Watson and Fowden (1975) and Soldal and Nissen (1978) demonstrated that plant roots could take up radio-labelled amino acids and others have confirmed these studies (reviewed by Miller et al 2007;Nacry et al 2013). Foliar uptake of amino acids has also been reported (Furuya and Umemiya 2002;Maini 2006;Stiegler et al 2013).…”
Section: Protein Hydrolysates and Amino Acidssupporting
confidence: 55%
“…Implicit in these studies is the assumption that plants can readily take up amino acids and peptides. Watson and Fowden (1975) and Soldal and Nissen (1978) demonstrated that plant roots could take up radio-labelled amino acids and others have confirmed these studies (reviewed by Miller et al 2007;Nacry et al 2013). Foliar uptake of amino acids has also been reported (Furuya and Umemiya 2002;Maini 2006;Stiegler et al 2013).…”
Section: Protein Hydrolysates and Amino Acidssupporting
confidence: 55%
“…Despite their importance-e.g., for the nutritional quality of seeds-synthesis and accumulation of lysine in seeds and import are poorly understood. Biochemical and genetic studies have provided evidence for carrier proteins mediating basic amino acid transport (32)(33)(34)(35)(36)(37). Complementation of a histidine uptake deficiency of yeast enabled the isolation and characterization of AAT1 that is homologous to amino acid transporters from bacterial, fungal, and mammalian but not plant origin.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids were applied at 24 h, rather than at 0 h, to reduce changes in nutrient exudation by germinating seeds. The composition of plant exudates results from the net influx and efflux of compounds by the plant (38); these influx and efflux rates can change in response to the external chemical environment (39). However, a study by Phillips et al (30) indicated that in germinating alfalfa, amino acid concentrations stabilize after 24 h, suggesting that by that time (i) the pool of amino acids available to microbes, i.e., S. enterica, for growth has already been released and (ii) the net concentration of plant-derived amino acids in seed/root exudates is less likely to be influenced by exogenous supplementation with the compounds.…”
Section: Discussionmentioning
confidence: 99%